The Impact of COVID-19 Pandemic During Lockdown on the Veterinary Profession in Romania: A Questionnaire-Based Survey - Mureşan, Alexandra Nicoleta; Morariu, Sorin; Baisan, Radu Andrei; Costea, Ruxandra; Mureşan, Cosmin (Frontiers in Veterinary Science, 2021)
The lockdown period in Romania lasted for 60 days and had the purpose of limiting the spread of SARS-CoV-2 virus outbreak and manage its consequences through emergency measures on many important areas of activity. This study aimed to gather, assess, analyze and disseminate relevant social, economic, and medical aspects on the impact of COVID-19 pandemic during lockdown on the veterinary profession in Romania. A survey was created using an online questionnaire platform, and disseminated. The survey was completed by a total of 409 individuals. A high number of respondents (71.64%; n = 293) felt exposed to medium or high risk of infection with SARS-CoV-2 at their workplace and many (56.97%; n = 233) felt that their professional environment was more stressful than usual during lockdown. Almost all respondents (89.73%; n = 367) declared the implementation of several control measures recommended by FECAVA and FVE (e.g. social distancing, wearing protective equipment, hand washing), but few mentioned the opportunity of remote work or visiting restrictions. Overall, the results show that the impact of lockdown lies directly on four main categories of importance on veterinarian professional’s life - human resource, activity management, relationship between veterinarian and authorities, and continuing education.